Studi Pemahaman Hadis Memakai Sandal Ketika Shalat - Firdayanti Firdayanti; Febriyeni Febriyeni (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
The research used is the library research method. The primary data sources in this study are hadiths about wearing sandals when praying, including the Sahih Bukhari Book, the Sahih Muslim Book, the Sunan Abu Daud Book, the Sunan Tirmidzi Book, the Musnad Ahmad bin Hambal, etc. The results of the studyHadith of wearing sandals when praying In this classification, the hadiths have the same wording and meaning, namely the statement of the Prophet praying using sandals. Hadith of not wearing sandals when praying In this classification of hadith, the Prophet took off his sandals during congregational prayers when the conquest of the city of Mecca and the actions of the Prophet were followed by his companions, and the reason the Prophet took off his sandals was because the Angel Gabriel told him that there was dirt on the Prophet's sandals. And it is explained in the sound of the hadith from another path, by rubbing the sandals on the ground in an effort to clean the sandals from dirt. And when taking off sandals it is advisable to prioritize the comfort of others. In terms of wording, the Prophet stated that he prayed with sandals and sometimes not. As for the prophet's editorial to differentiate (differentiate) between Muslims and Jews, the Prophet ordered to wear sandals when praying. In historical, sociological and anthropological context. The space and time when the Messenger of Allah performed or recited the hadith of wearing sandals when praying, in the early period of Islam there were not so many mosque buildings built and still had pedestals, so the Messenger of Allah gave concessions (rukhsah) on the face of this earth to create a mosque that could be used as a place of prayer. So it is possible to wear a khuf or na'lun when praying with the condition that it must be pure from the major and minor hadas. If we look at modern times, mosques have been built with ceramic or floor coverings.